2019
DOI: 10.3233/jad-180983
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Treatment Initiation and Healthcare Costs in Alzheimer’s Disease

Abstract: The relationship between Alzheimer's disease (AD) treatment patterns and healthcare costs is unknown. Administrative claims data from the MarketScan Commercial and Medicare databases covering 2010 through 2016 were used to identify the comorbidities, treatment patterns, and healthcare costs in the three years prior to and one year post medical diagnosis of AD in 21,448 patients with no treatment and 57,970 patients with treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Early intervention improves the clinical benefits for patients with AD [ 46 48 ]. Actively managing the risk factors, such as preventing and treating depression, quitting smoking, preventing hearing loss, stabilizing blood pressure, managing blood glucose, maintaining a reasonable diet, ensuring enough sleep, and encouraging regular physical exercise, have considerable significance in reducing and delaying the development of AD [ 5 , 49 ].…”
Section: Comprehensive Ad Managementmentioning
confidence: 99%
“…Early intervention improves the clinical benefits for patients with AD [ 46 48 ]. Actively managing the risk factors, such as preventing and treating depression, quitting smoking, preventing hearing loss, stabilizing blood pressure, managing blood glucose, maintaining a reasonable diet, ensuring enough sleep, and encouraging regular physical exercise, have considerable significance in reducing and delaying the development of AD [ 5 , 49 ].…”
Section: Comprehensive Ad Managementmentioning
confidence: 99%
“…A model evaluating the relationship between time to institutionalization and total societal costs estimated that total monthly direct costs rose from £770 at 5 years before institutionalization to £1529 at institutionalization, with healthcare costs accounting for relatively little of the increase (£283 to £348) [ 78 ]. Two retrospective database analyses conducted in the USA found that direct costs were higher among patients with clinically diagnosed AD dementia aged 65 to 100 years who received a Food and Drug Administration (FDA)-approved treatment compared with those who did not [ 91 , 92 ]. One study found that total direct costs were significantly higher among untreated patients (PPPM costs $2509 vs. $2152, p = 0.0162) [ 91 , 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two retrospective database analyses conducted in the USA found that direct costs were higher among patients with clinically diagnosed AD dementia aged 65 to 100 years who received a Food and Drug Administration (FDA)-approved treatment compared with those who did not [ 91 , 92 ]. One study found that total direct costs were significantly higher among untreated patients (PPPM costs $2509 vs. $2152, p = 0.0162) [ 91 , 92 ]. The other analysis, which also stratified patients by age and timing of treatment initiation, found that patients aged 65 to 100 years who were not treated incurred higher costs than those who were treated (PPPM costs: untreated: $2744, treated: $2029 to $2706 depending on timing of treatment initiation) [ 92 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…( 6) A psychological education plan should be developed, and cognitive behavioral therapy should be used to encourage caregivers to learn psychological relaxation techniques, which are beneficial to both the patients and caregivers [88,89] (III) Addressing financial burdens: (1) The financial burden and relevant factors related to the care of patients with dementia should be assessed to provide a reference for the development of proper medical care plans, new health care policies, social resource support plans, and medical insurance plans [90,91]. (2) According to previous studies, antidementia medication can reduce medical costs, which then reduces the caregiver's financial burden [92]. (3) Improving the care abilities and financial status of caregivers might also alleviate their financial burden.…”
Section: Methods Of Addressing Caregiver Stressmentioning
confidence: 99%